INFLATION IMPACT OF FOOD PRICES: CASE OF SERBIA - Šoškić, Dejan (Economics of Agriculture, 2015)
Food prices traditionally have an impact on inflation around the world. Movements in these prices are coming more from the supply side, then from the demand side. If treated as a supply shock, monetary policy should not react. However, food prices are part of headline inflation that is an official target for most central banks. Serbia conducts Inflation targeting and faces serious challenges with food price volatility. Food price volatility in Serbia hampers inflation forecasting, and may have a negative influence on inflationary expectations and public confidence in (i.e. credibility of) the Central bank, all of crucial importance for success of Inflation targeting. There are several important possible improvements that may decrease volatility of food prices but also limit negative impact of food price volatility on Consumer Price Index (CPI) as a measure of inflation. These improvements are very important for success of Inflation targeting in Serbia.